Images and objects of evangelization: The Peruvian Amazonian Religious Imaginary in the Colonial Period - Aburto Cotrina, Carlos Oswaldo (2004)
Although these people who are raised in ignorance and customs that I have pointed out, show signs of skill in the things that they need or to which their appetite takes them, as with the weapons they use, which make them curious carving the chontas like with burin and around, with only little bones that serve them as tools and snails for brush. The canoes, which take them out proportionately, especially some nations, make them as a level; many of the fabrics that they weave to cover themselves, thin, with beautiful work and paintings; the garlands of various colors of feathers, which they call llautos; the clay pots they use are well made and painted.